Occupational Segregation and Declining Gender Wage Gap : The Case of Georgia - Khitarishvili, Tamar; Rodriguez-Chamussy, Lourdes; Sinha, Nistha (World Bank, Washington, DC, 2018)
This paper examines the role of industrial and occupational segregation in explaining the gender wage gap and its evolution in Georgia between 2004 and 2015. It first documents the declining trends observed in the gender wage gap in Georgia during this period, commenting on some of the possible underlying factors driving such trends. It then presents evidence that employment patterns by industry and occupations are highly concentrated in the country and measures the degree of segregation using the Duncan index. Next, it analyzes if and how much industrial and occupational segregation have contributed to the gender wage gap and its decline by decomposing the gender wage gap into the within-category and between-category components. The results point to existing gender wage gaps within sectors, industries, and occupations being the primary drivers of the wage gap in Georgia, and find a smaller role of gender segregation per se in these categories.